2018
DOI: 10.1007/s00284-018-1522-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Legiolert for Quantification of Legionella pneumophila from Non-potable Water

Abstract: Legiolert® is a new culture method for quantification of Legionella pneumophila, which is the primary species associated with Legionnaires’ disease. The test is based on a most probable number approach, and differs significantly from traditional culture methods by providing results at 7 days, rapid sample preparation and analysis, and objective interpretation of test results. In this study, we compared the performance of Legiolert with the U.S. Centers for Disease Control and Prevention (CDC) method for detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 24 publications
4
32
0
Order By: Relevance
“…The true positivity rate in this study (rounds 1 and 2) was lower than the Legiolert specificity reported by Sartory et al (), where 14 of 290 premise water samples (4.8%) did not serotype as a L. pneumophila strain, or by Spies et al (), who reported that the Legiolert method had a specificity for L. pneumophila of 97.9% (2.1% nonconfirming) for premise samples, both of which are comparable to the 95.3% specificity for the ISO 11731 method. Legiolert nonpotable evaluations have primarily been conducted with cooling towers, for which the true positivity rate was reported to be 95.1% (Rech et al, ). The differences observed in this study for both the potable and nonpotable evaluations compared with other published results are likely derived from both the novel sample types evaluated and the paucity of overall positive samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The true positivity rate in this study (rounds 1 and 2) was lower than the Legiolert specificity reported by Sartory et al (), where 14 of 290 premise water samples (4.8%) did not serotype as a L. pneumophila strain, or by Spies et al (), who reported that the Legiolert method had a specificity for L. pneumophila of 97.9% (2.1% nonconfirming) for premise samples, both of which are comparable to the 95.3% specificity for the ISO 11731 method. Legiolert nonpotable evaluations have primarily been conducted with cooling towers, for which the true positivity rate was reported to be 95.1% (Rech et al, ). The differences observed in this study for both the potable and nonpotable evaluations compared with other published results are likely derived from both the novel sample types evaluated and the paucity of overall positive samples.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, IDEXX Laboratories Inc. (Westbrook, ME) developed a culture‐based assay for the enumeration of L. pneumophila that is easy to use by water utilities (LeChevallier, ). The test has been shown by several researchers to result in equivalent or higher counts of L. pneumophila from potable, nonpotable, and water cooling tower samples (Petrisek & Hall, ; Rech, Swalla, & Dobranic, ; Sartory, Spies, Lange, Schneider, & Langer, ; Spies et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…IDEXX Legiolert is a relatively newly developed culture method used for the detection of L. pneumophila and, when comparing sensitivity of confirmed positive samples in prior studies to conventional culture methods, Legiolert tended to yield better sensitivity in in potable water samples (Sartory et al 2017). Legiolert similarly exhibited higher sensitivity in potable water samples (Petrisek and Hall 2018) and equivalent sensitivity in non-potable water samples compared to plate culture methods (Petrisek and Hall 2018;Rech et al 2018). While the results herein were unexpected, the number of overall positive comparative data points was small and, as such, an expanded sample size would be more informative for comparative performance with matrices like well water, which have not been previously validated with Legiolert.…”
Section: Culture and Molecular Methods Comparisonmentioning
confidence: 99%
“…Similarly, for the nonpotable water analysis, Legiolert had a false positivity value of <0.9% and a specificity of 100%. Similarly, Rech, Swalla, and Dobranic () reported increased sensitivity, low false positive rates, and less interference for nonpotable water cooling tower samples than the Centers for Disease Control and Prevention (CDC) culture method.…”
Section: Introductionmentioning
confidence: 98%